Endothelial dysfunction in individuals born after fetal growth restriction: cardiovascular and renal consequences and preventive approaches. (2nd May 2017) - Yzydorczyk, C.; Armengaud, J. B.; Peyter, A. C.; Chehade, H.; Cachat, F.; Juvet, C.; Siddeek, B.; Simoncini, S.; Sabatier, F.; Dignat-George, F.; Mitanchez, D.; Simeoni, U.
Abstract : Individuals born after intrauterine growth restriction (IUGR) have an increased risk of perinatal morbidity/mortality, and those who survive face long-term consequences such as cardiovascular-related diseases, including systemic hypertension, atherosclerosis, coronary heart disease and chronic kidney disease. In addition to the demonstrated long-term effects of decreased nephron endowment and hyperactivity of the hypothalamic–pituitary–adrenal axis, individuals born after IUGR also exhibit early alterations in vascular structure and function, which have been identified as key factors of the development of cardiovascular-related diseases. The endothelium plays a major role in maintaining vascular function and homeostasis. Therefore, it is not surprising that impaired endothelial function can lead to the long-term development of vascular-related diseases. Endothelial dysfunction, particularly impaired endothelium-dependent vasodilation and vascular remodeling, involves decreased nitric oxide (NO) bioavailability, impaired endothelial NO synthase functionality, increased oxidative stress, endothelial progenitor cells dysfunction and accelerated vascular senescence. Preventive approaches such as breastfeeding, supplementation with folate, vitamins, antioxidants, L-citrulline, L-arginine and treatment with NO modulators represent promising strategies for improving endothelial function, mitigating long-term outcomes and possibly preventing IUGR of vascular origin. Moreover, the identification of early biomarkers of endothelial dysfunction, especially epigenetic biomarkers, could allow early screening and follow-up of individuals at risk of developing cardiovascular and renal diseases, thus contributing to the development of preventive and therapeutic strategies to avert the long-term effects of endothelial dysfunction in infants born after IUGR.